Fracture toughness of 304L austenitic stainless steel produced by laser powder bed fusion - Kumar, Punit (2022)
Uniaxial tensile response and J integral–resistance behavior of 304L austenitic stainless steel manufactured by laser powder bed fusion process (LPBF) were investigated. The steel undergoes transformation induced plasticity (TRIP) at room temperature, resulting in high fracture toughness (JQ) values combined with high strength (σY) and ductility. Upon increasing the temperature to 75°C, TRIP becomes inactive, and the deformation mechanism is dominated by dislocation glide and twinning. This leads to a substantial reduction in JQ and marked anisotropy, while σY remains unchanged. Significance of these results in terms of fracture properties of steels manufactured via LPBF processes is discussed.